Molecular taxonomy and intra-Palaearctic boundary: new insights from the biogeography of the black francolin (Francolinus francolinus) by means of microsatellite DNA. Issue 8 (17th November 2019) - Forcina, Giovanni; Guerrini, Monica; Panayides, Panicos; Hadjigerou, Pantelis; Khan, Aleem Ahmed; Barbanera, Filippo
Abstract : The transition zones between and within biogeographic realms are a topical issue. Long ascribed to eastern Palaearctic, Iran was recently proposed as entirely pertaining to its western counterpart (featuring the ´Great Western Palaearctic`). Molecular and phenotypic information from polytypic taxa may help untangle the bioclimatic and environmental dynamics that shaped faunal distributions. In this study, we collected 221 black francolin ( Francolinus francolinus Linnaeus, 1766) samples from Cyprus to Bangladesh and compared the spatial genetic structure as inferred from nine microsatellite loci with publically available bioacoustic data. We found striking overlap between the two sources of information, which pointed to the occurrence of a western and an eastern subdivision ( F ST = 0.435, P  < 0.001) with a break across central Iran. When framed within the palaeoclimatic and geomorphological history of this region, we found that high connectivity among local subspecies was facilitated by warmer and more humid conditions preceding the cold-arid climatic phase associated with the last glacial stage. The subsequent temperature increase likely led to the substantial isolation of eastern and western black francolin populations to moist refuges. Overall, these results point to an intra-Palaearctic boundary crossing Iran longitudinally, thus raising prospect of compromise between the two most debated views.